Yahoo Web Search

  1. Sort by

  1. |r(t)| = constant implies that 1. r(t) either doesn't change with t, r'(t)=0 or 2. its...would change also by the triangle inequality. In either case since 1. r'(t)=0 or 2. r(t) dot r'(t) = r(t)r'(t)cos(90) = 0...

    1 Answers · Science & Mathematics · 17/04/2015

  2. r^2+3r-2 = 0 Factorize the equation. then (r+1)(r-3) = 0 Therefore, r = -1 & 3

    3 Answers · Science & Mathematics · 14/10/2008

  3. R' or also known as R-prime can, but doesn't always have to be the original R. It's there to show you that you can place any other alkane substitute in that...

    3 Answers · Science & Mathematics · 24/04/2010

  4. 0.2 + r = 0.2r − 0.06 + 0.3r Fist, let's simplify the right side side: r + 0.2 = 0.5r − 0.06 Next, isolate r and simplify. (r + 0.2) - 0.5r - 0.2...

    12 Answers · Science & Mathematics · 16/10/2007

  5. ... consists of: r = radius measure(magnitude) theta = angle measure(... ( a , ib) is now ( r*cos(theta) , r*sin(theta) Finally: your answer...

    2 Answers · Science & Mathematics · 31/05/2008

  6. description of r: look at the figure where potential is required at point P ...)----------------------. (P) .... <-----------r---------> r & Q are given k = 8.987 X 10^9 N...

    3 Answers · Science & Mathematics · 01/02/2011

  7. I = (2V/R) + 2r I - (2V/R) = 2r r = (1/2) * [I - (2V/R... - IR r = (2V - IR) / 2I r = (V/I) - (R/2)

    3 Answers · Science & Mathematics · 16/01/2014

  8. C=K(Rr/R-r) Divide both sides by K: C/K = (Rr... = Cr/K Extract R: R(C/K - r) = Cr/K Divide both sides by (C/K - r...

    4 Answers · Education & Reference · 05/10/2009

  9. If f is a *surjective* homomorphism from R to R' then R/ker(f) and R'...ker(f) to f(x) is an isomorphism--- so, in particular, R/ker(f) is isomorphic to f(R). But...

    1 Answers · Science & Mathematics · 24/07/2011

  10. r-(13/3)=(3/2) r=(3/2)+(13/3) r=(9/6)+(26/6) r=35/6 r=5.8333 or 5 and 5/6

    3 Answers · Science & Mathematics · 06/11/2009

  1. Try asking your question on Yahoo Answers